DATABASE PROTECTION USING DBP ROTECT SOFTWARE - Khryshchevsky, R; Nesterenko, Kateryna; Kozlovsky, Valerii; Tkalya, Olena (Science-based technologies, 2022)
Information is one of the most important resources in the modern world. Since information technologies are developing and the number of threats is increasing, therefore, the question of improving its protection is obvious in order to prevent damage to the interests of the information owner. Statistics show that in recent years, the number of hacks and information leaks has greatly increased. which leads to large financial losses or to the disclosure of passport data and other personal documents. In the scientific and commercial spheres, leaks of information through unauthorized access lead to the appropriation of other people's works and the disclosure of commercial secrets, which causes great losses. Therefore, confidential information needs protection and control. Since an incredibly large amount of information is now circulating in the information space for ease of use, organizations are implementing databases. A database is the best method for working with a large amount of information, which is a systematized collection of materials of various types for processing using a computer. The criminal sphere is developing as evidenced by the statistics, according to which in the last years the number of hacks and information leaks has increased greatly. Although the number of recorded and confirmed cases of hacking is incredibly high, many cases are hushed up to preserve reputation. Therefore, sensitive information requires protection and control to ensure security. One of the options for companies and organizations to protect their data is to use various platforms created specifically to identify database vulnerabilities and prevent unauthorized interventions. The DbProtect software package is perfect for both small companies and medium and large organizations. DbProtect serves to resolve database security issues and ensure that all requirements are met in accordance with regulations. This platform is designed to be able to fulfil all the needs of various database systems.